Fish in Kongsfjorden under the influence of climate warming - Gorska, Natalia; Schmidt, Beata; Węsławski, Jan Marcin; Grabowski, Miłosz; Dragan-Górska, Agata; Szczucka, Joanna; Beszczynska-Möller, Agnieszka (Frontiers in Marine Science, 2023)
Introduction Kongsfjorden is being impacted by climate warming, which has fostered the increase of abundance of Atlantic fish (e.g. Atlantic cod, Gadus morhua), fish that are non-endemic for Kongsfjorden. The growth and high predation potential of Atlantic fish may affect the survival of polar cod (Boreogadus saida), native species of the Kongsfjorden, a species with ecological and economic value. This means that it is important to monitor the impact of climate change on the fjord fish community. This, as well as the experience of the successful use of hydroacoustic techniques in the fjord, encouraged us to continue in 2022 the hydroacoustic study of fish that began in 2013 and 2014. Our main goal was to understand and confirm how the fish community in Kongsfjorden has changed over the last decade under the influence of global warming. Methods Our approach aimed not only to replicate the previous research conducted in 2013 and 2014, based on the same methodology for collecting and analyzing hydroacoustic data, but also to compare the newly acquired data with the results available in the previous publications. The histograms of fish target strength (a measure of sound backscatter by an individual) were analyzed and the fish spatial distribution (regarding thermohaline structure and “predator-prey” relationships) was acoustically observed. Results The presence of native polar cod and non-endemic Atlantic cod in the Kongsfjorden was shown. Furthermore, during the study period, an increase in fish size diversity was observed, which suggests change in the food web and a decline in native polar cod. It was confirmed that the process of establishment of non-Arctic species Atlantic cod in Kongsfjorden continues. Discussion We went beyond the spatial and temporal constraints of previous Kongsfjorden studies, taking into account fjord fish communities over a wider area and over the long term. Therefore, our understanding of climate warming impact on the fish community of Kongsfjorden has been deepened. Further progress necessitates annual hydroacoustic observation of the fjord fish community accompanied by biological sampling.